Relações de liderança no mundo do trabalho - Monastersky, Roberto (2015)
This dissertation aims to study the power relations within organizations, whose structure of hierarchical authority raises the managers, with the role of maintaining the power while controlling the workforce and seek subterfuges to increase productivity and profits. Unlike the leaders, these managers do not support the workers to develop an entrepreneurial behavior, either to meet their needs for self-esteem and self-actualization through work. This work is based on the studies of sociology of work and organizational psychology whereby the leadership relations promote personal and professional development of the employee, and therefore serve to increase productivity in business organizations. The case study was conducted at Enger Engenharia, a specialized business organization in project management and supervision for the construction industry, whose headquarter is located in Alphaville (Barueri SP). At the time of our contact with the ENGER were interviewed 127, which represents the majority of the staff of the company. On the other hand, aiming to build this case study, we interviewed in greater depth three workers, that is, a true leader and two direct reports to him. The answers provided by respondents prove the truth of the guiding hypothesis of the study that true leaders are vectors of personal and professional growth of the employee and consequently of business development